NAVIGATING TEACHING DURING PANDEMIC: THE USE OF DISCUSSION FORUM IN BUSINESS ENGLISH WRITING CLASS - Anastasia Nelladia Cendra; Eric Sulindra (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2022)
To response the spread of Covid-19, almost all offline education institutes are shut down and e-learning is conducted almost abruptly, including in a Business English writing class for university students. The discussion forum in the LMS ‘Moodle’ is used a lot to help the discussion of this class alive. To widen the knowledge of the use of discussion forum, especially during an emergency time like this Covid-19 pandemic, this qualitative descriptive qualitative research aims to explore how discussion forum is used in the LMS ‘Moodle’ for university students in e-learning during a pandemic, especially concerning optimization of the questions, the arrangement of the topics of discussion, and the assignments. By analyzing the patterns of how the discussion forum is used and interviewing the students, this research found that what determines the student's response to the discussion in the forum is the question words and the key words in the discussion sentences in the forum. These two things will determine students’ answers in terms of the key words used by students, the length and shortness of student answers, and the type and depth of student answers, which in turn show how students interact in the discussion forum.